Studies on Water-Use Efficiency and Energy Gain of Some Crops Grown in Sikar District - Dutta, Dibyendu; Das, S N; Pathak, S; Sharma, J R (Annals of Arid Zone, 2016)
Relative suitability of six crops (maize, pearl millet, mung bean, gram, wheat and mustard/toria) grown at Neem Ka Thana tehsil of Sikar district were evaluated with respect to their consumptive water need, energy use scenario and water-use efficiency under rainfed conditions. Among Blaney-Criddle, Radiation and Thomthwaite methods, the first one agreed well with Mo-Penman method in all the seasons, except during summer and could be used for calculation of PET. The variability among different methods of calculating PET was less (cv = 16.51%) in kharif than in rabi crops (cv = 28.21%). Toria always had minimum water requirement while maize and pearl millet had comparatively higher water requirement with no definite order. In kharif season, mung bean was found to be the highest gainer of energy and harvested photosynthetically active radiation most efficiently, whereas, during rabi, all the crops had positive energy balance and gram was the highest energy gainer (+ 238 mm, average of four methods). Wheat had the.highest water-use efficiency among kharif and rabi crops. Considering water requirement, energy gain and water-use efficiency, mung bean was the best selection during kharif and toria mustard during rabi season.